2020
DOI: 10.1111/lapo.12142
|View full text |Cite
|
Sign up to set email alerts
|

Worthy of Justice: A Veterans Treatment Court in Practice

Abstract: This article examines the purpose and practice of a Veterans Treatment Court (VTC), a new type of problem-solving court designed to connect qualifying former service members in the criminal justice system with social services. While existing studies of VTCs explain these courts by focusing on veterans' distinct needs or deservingness based on their military service, this article argues that these courts are being created because of societal beliefs about veteran worth. By revealing how court staff, participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 61 publications
(49 reference statements)
1
6
0
Order By: Relevance
“…Court actors intervened on behalf of participants, even circumventing organizations’ bureaucratic requirements, such as when the judge intervened to get necessary medicine in Eduardo's case. These findings align with how ideas of deservingness in participants are constructed and prompt when actors intervene (Rowen, 2020).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Court actors intervened on behalf of participants, even circumventing organizations’ bureaucratic requirements, such as when the judge intervened to get necessary medicine in Eduardo's case. These findings align with how ideas of deservingness in participants are constructed and prompt when actors intervene (Rowen, 2020).…”
Section: Discussionsupporting
confidence: 72%
“…Similarly, Halushka (2017) found that reentry organizations “responsibilize” clients, making them accountable for their own success through self-discipline, even as policies constrain individuals’ autonomy (Miller and Stuart, 2017; Turnbull and Hannah-Moffat, 2009; Werth, 2011). In this way, parole and other reentry organizations both responsbilize and de-responsibilize clients (Cox, 2011; Rowen, 2020; Turnbull and Hannah-Moffat, 2009; Werth, 2011). Participants must also have a “cooperative, willing attitude” while engaging in these activities to demonstrate that they are productive and civically engaged members of society (Werth, 2011: 332).…”
Section: Individualization Of Responsibilities and Internal Metricsmentioning
confidence: 99%
“…Thus, although VTC participants typically address the same behavioral health conditions as do participants in other treatment courts, the esteem conferred by their military service can buffer against stigma-laden diagnoses. Rowen (2020) termed military service "the main criterion for [VTC] entry" (p. 80) in arguing that VTCs have proliferated due to the perceived moral worth of veterans.…”
Section: Veterans Treatment Courtsmentioning
confidence: 99%
“…These findings may have been affected by a small sample, low rate of recidivism, and positive skew in the study's measure of procedural justice. Rowen (2020) conducted a qualitative study of one VTC and drew on procedural justice theory to understand court attempts to encourage veteran compliance.…”
Section: Procedural Justice Theorymentioning
confidence: 99%
“…We argue that PDPs—and, by implication, problem‐solving justice more broadly—demonstrate how people with disparate professional and political orientations exhibit what we call “targeted sympathy.” PDP professionals respond to the dissonances between their criminal justice roles and their personal and professional ethics and, like other street‐level bureaucrats, use moral entrepreneurship within their circumscribed decision‐making authority (Hasenfeld, 2000). Drawing on their expertise, they allocate limited resources to a subset of potential beneficiaries in ways that respond to their determinations of deservingness (Corrigan & Shdaimah, 2016; Rowen, 2020). While some defendants therefore benefit from sympathetic PDPs, problem‐solving justice also participates in the construction of ideal subjects, a feature of neoliberal governance that absolves the state of responsibility for individual and social welfare while creating a more compliant citizenry (Dewey & Germain, 2016; Soss et al, 2011; Leon & Shdaimah, 2012).…”
Section: Introductionmentioning
confidence: 99%